RNA m5C modification: from physiology to pathology and its biological significance - Chen, Xi; Yuan, Yixiao; Zhou, Fan; Huang, Xiaobing; Li, Lihua; Pu, Jun; Zeng, Yong; Jiang, Xiulin (Frontiers in Immunology, 2025)
RNA 5-methylcytosine (m5C) modification is a crucial epitranscriptomic mark that regulates RNA stability, processing, and translation. Emerging evidence highlights its essential role in various physiological processes, including cellular differentiation, stem cell maintenance, and immune responses. Dysregulation of m5C modification has been implicated in multiple pathological conditions, particularly in cancer, neurodegenerative disorders, and metabolic diseases. This review provides a comprehensive overview of the molecular mechanisms governing m5C deposition, its functional consequences in normal physiology, and its contributions to disease pathogenesis. Furthermore, we discuss the potential of m5C as a biomarker and therapeutic target, offering new insights into its biological significance and clinical relevance.